Utilization and Effectiveness of Computer Network to Support Productivity at Politeknik Pelayaran Surabaya - Yudianto, Prima Yudha; Dwi Santoso, Agus; Harianto, Bambang Bagus (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
In the implementation of learning and operational parchment, the need for an adequate computer network is a must and a fundamental need. Technology in the current era already covers all aspects of life. To support office activities and lectures, the teaching and learning process and other supporting processes have used information technology as a backbone and means of communication. Poltekpel Surabaya has implemented various applications both in office and learning processes, examples of applications are: SIAKAD Application (Academic Information System), SiPopeye Online Registration Application, P3M application and other application applications. The quality of the Surabaya Shipping Polytechnic network can be seen from the Quality of Service (QoS) network with parameters, namely, average Troughput: 164.92 Mbps, with an average packet loss: 12.75% and an average delay: 2.97 ms. With data retrieval as much as 12 times